2006
DOI: 10.3748/wjg.12.4918
|View full text |Cite
|
Sign up to set email alerts
|

A case of mucin producing liver metastases with intrabiliary extension

Abstract: A 75-year-old man was admitted to our hospital with a diagnosis of liver metastases from colon cancer. He underwent right hemicolectomy for cecal cancer eight years ago, and had a metastatic liver tumor in segment 8 (S8), which was surgically resected about 4 years after the initial operation. Histopathological examination of the resected specimens from both operations revealed a welldifferentiated adenocarcinoma with mucinous carcinoma. Four months after the second operation, computed tomography demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…3,5,6,8,15 Tumor growth confined to the bile duct, as in the present case, has rarely been described. 3,5,16 Itatsu et al 3 and Blumgart et al 16 Nanashima et al, Page 7 provided summaries of a small number of cases.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…3,5,6,8,15 Tumor growth confined to the bile duct, as in the present case, has rarely been described. 3,5,16 Itatsu et al 3 and Blumgart et al 16 Nanashima et al, Page 7 provided summaries of a small number of cases.…”
Section: Discussionmentioning
confidence: 56%
“…[3][4][5][6][7] The morphology of this tumor resembled a rare biliary carcinoma termed "intraductal papillary neoplasm of the bile duct" (IPNB) by Nakanuma and Chen et al 8,11,12 As in IPNB, the tumor in the present report showed marked dilatation of the bile duct without jaundice was observed with or without mucin secretion. 11,12 The histological findings of intraductal papillary growth of liver metastasis were also similar to IPNB as a papillary proliferation of carcinoma in the epithelium.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations